Pengaruh Media Pembelajaran Online Wordwall Terhadap Kemampuan Mengenal Konsep Bilangan: Anak Usia 5-6 Tahun di TK Kihajar Dewantoro VII Kecamatan Kota Tengah Kota Gorontalo - Yusrin R. Mustapa; Pupung Puspa Ardini; Rapi Us. Djuko (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study examined the effect of wordwall online learning media on recognizing numbers in children aged 5-6 years at Kihajar Dewantoro VII Kindergarten, Kota Tengah Sub-District, Gorontalo City. This study aimed to discover whether wordwall learning media affects the ability to recognize the concept of numbers in children aged 5-6 years. This quantitative research used an experimental research method with a one-group pretest-posttest design. The data in this study was collected through test observation. The subjects of this study were 16 children at the age of 5-6 years. Based on the analysis of the t-test (paired sample t-test), it was found that the t-count was greater than the t-table (24.744 > 2.201 and sig. (2-tailed) = 0.000<0.05). From this result, HO was rejected, and Ha was confirmed. In conclusion, wordwall learning media affected the ability to recognize the concept of numbers in children aged 5-6 years at Kihajar Dewantoro VII Kindergarten, Kota Tengah Sub-District, Gorontalo City.